EFEKTIVITAS PENERAPAN KOOPERATIF PICTURE AND PICTURE DALAM MENINGKATKAN HASIL BELAJAR MATA PELAJARAN IPS SMP - Lestari, Novi Ayu; Matsum, Junaidi H.; Noor, Agus Sastrawan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted based on the observation that learning carried out in the classroom on social studies subjects is always done by only using the lecture method. This study aims to determine the effectiveness of the application of the cooperative learning model picture and picture in improving student learning outcomes in social studies subjects in class VII of 12 Middle School in Siak Hamlet, Durian Village, Sungai Ambawang District, Kubu Raya District. The method used is Quasi Experiment Design with the research design used is Nonequivalent Control Group Design. The sample of this study was 52 students. The results of data analysis showed that student learning outcomes between the experimental class and the control class did not experience significant differences. Evidenced by the results of the average post-test seen in the untreated control class that is 70. In the experimental class that was treated by using the cooperative learning model picture and picture the average post-test score of students was increased by 80. This is proportional straight with the level of effect size obtained that is equal to 0.659. This achievement is classified as moderate. This means that student learning outcomes using cooperative learning models picture and picture and learning outcomes of students who do not use the cooperative learning model picture and picture are not much different. Keywords: Effectiveness, Learning Model, Picture and Picture Cooperative, Learning Outcomes